2024
DOI: 10.1186/s13613-024-01249-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular epidemiological features of critically ill patients with invasive group A Streptococcus infections: a Belgian multicenter case-series

Marijke Peetermans,
Veerle Matheeussen,
Cedric Moerman
et al.

Abstract: Background Recent alerts have highlighted an increase in group A streptococcal (GAS) infections since 2022 in Europe and the United States. Streptococcus pyogenes can cause limited skin or mucosal disease, but can also present as severe invasive disease necessitating critical care. We performed a multicenter retrospective study of patients with GAS infections recently admitted to Belgian intensive care units (ICUs) since January 2022. We describe patient characteristics and investigate the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…Accordingly, we observed that in our cohort emm1/ST28 was the predominant variant, present in most patients (5/7) who died from an iGAS infection. Interestingly, we did not find any clusters originating from the three reference strains refM1uk, ref5005 and ref5448, known to cause invasive infections [9,37,38]. Furthermore, the phenotypic susceptibility testing revealed a high susceptibility to penicillin, erythromycin and clindamycin, confirming the known susceptibility patterns over the years without a shift towards more resistant strains, as reported worldwide [4,6,9].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Accordingly, we observed that in our cohort emm1/ST28 was the predominant variant, present in most patients (5/7) who died from an iGAS infection. Interestingly, we did not find any clusters originating from the three reference strains refM1uk, ref5005 and ref5448, known to cause invasive infections [9,37,38]. Furthermore, the phenotypic susceptibility testing revealed a high susceptibility to penicillin, erythromycin and clindamycin, confirming the known susceptibility patterns over the years without a shift towards more resistant strains, as reported worldwide [4,6,9].…”
Section: Discussionsupporting
confidence: 81%
“…The current hypothesis suggests that the lack of exposure to GAS and common seasonal respiratory viruses during the COVID-19 pandemic, due to isolation measures, resulted in decreased immunity to GAS and seasonal respiratory viruses [35, 37, 43, 45]. After lifting the COVID-19 pandemic protection measures, an increase and a shift of the seasonal pattern in seasonal respiratory viral and iGAS infections was observed after two years of their historically low incidence.…”
Section: Discussionmentioning
confidence: 90%